Effects of standardized extracts of Lamium album and Urtica dioica on rat tracheal smooth muscle contraction - Samane Arefani; Seyyed Mohammad Mohseni Mehran; Hassan Moladoust; Mohammad Reza Norasfard; Ahmad Ghorbani; Mahmood Abedinzade (Korean Pharmacopuncture Institute, 2018)
Objective: Diseases of the respiratory system are one of the main causes of death and include situation such as chronic obstructive pulmonary disease, pneumonia or asthma. Medicinal plants have beneficial effects on multiple diseases include respiratory disorders like asthma and bronchitis. The aim of this study was to evaluate the effects of U. dioica and L. Album on tracheal smooth muscle contraction. Material and methods: Hydroalcoholic extracts of L. Album and U. Dioica aerial parts were prepared by maceration method and standardized based on their total phenol content. The effect of the extracts on the KCl-induced contraction of rat trachea was examined in an organ bath chamber. Data was analyzed with spss software 22. Results: The extract of L. Album (5 mg/ml), similar to theophylline (20 mM), significantly reduced the KCl-induced tracheal contraction. On the other hand, U. Dioica (1 mg/ml and 5 mg/ml) augmented the KCl-induced contraction. Conclusion: The relaxant effect of L. Album on the trachea makes it as a candidate for the managing patients with asthma and obstructive pulmonary diseases. But because of U. Dioica potential constrictive effect on the trachea it is suggested that patients avoid consuming it.